Ethnomathematic Exploration Of Minangkabau Batik Tanah “Liek” (Clay Soil Batik) - Isnaniah; M. Imamuddin (International Journal Of Humanities Education and Social Sciences (IJHESS), 2023)
Ethnomathematics in mathematics learning is becoming a trend in Indonesia. Learning mathematics with ethnomathematics is nothing but introducing and learning mathematical concepts through local culture. This research belongs to qualitative research with an ethnographic approach. The purpose of this research is to explore the mathematical concepts found in batik tanah like (clay soil batik). Data in this study were collected by observation, documentation and interviews. Data analysis was carried out with the steps of data reduction, presentation, interpretation, and exposure. The result of this research is that in the motifs of batik tanah "liek" many geometry concepts are found such as: point, line, curved line, parallel line, triangle, rectangle, square, circle, angle, opposite angle, symmetry and kesebangunan. Different motifs have different geometry concepts. The findings of geometry concepts in batik tanah "liek" can be used as a learning resource in learning mathematics. Using learning resources that are in accordance with student culture can make learning meaningful and can increase love for local culture.